Analisis Psikologi Sastra Dalam Novel Sin: God Hates The Sin, Not The Sinner Karya Faradita - Rahma, Amalia Nur; Hefni, Asnan; Setyawati, Meita (Universitas Mulawarman, 2021)
Novel is a work of fiction that tells the life of a character. Therefore, one of the important elements in the novel is the character. This study aims to describe the psychology of the main and additional characters in the SIN novel